Avaliação do risco para desenvolvimento de úlcera por pressão em idosos institucionalizados - Ribeiro, Jackeline Kércia de Souza (2013)
A pressure ulcer (PU), important harm found in the institutionalized elderly population, and increases spending on care, has important repercussions in their lives, such as increased morbidity and decreased quality of life. The elderly are more susceptible to developing PU, because of changes that occur with aging, especially in the skin. This is a cross-sectional, observational, descriptive predominantly, quantitative approach and aimed to determine the prevalence and risk factors for the development of pressure ulcers in institutionalized elderly. It was developed with 160 individuals, aged 60 or older, living in two long-stay institutions for the elderly (nursing home) city of João Pessoa. Data were obtained through physical examination, interview and analysis of medical records. The data analyses were obtained distributions absolute percentage unitary and bivariate and inferential statistical techniques. The data collected were organized in Microsoft Excel and exported into Statistical Package for Social Sciences (SPSS) 20.0. The literature review included national and international scientific articles, thesis and dissertation. Most seniors were female (67.5%) with mean age of 81.9 years old, literate (36.9%), colored or white (55%), single (49.4%) , retired (91.4%), sent to institutions by relatives (45.6%) and used for the SUS access to health services (56.9%). There was a predominance of cardiovascular diseases (65.6%) and use of psychotropic medication (65%). Among the risk factors, showed statistical significance for the presence of PU: dependence on position change (p<0,001), fecal (p=0,004) and urinary incontinence (p=0,001), cognitive impairment (p=0,013) and physical limitations (p=0,030). The PU prevalence in this population was 7.5%, the anatomical locations of higher frequencies were gluteal region (49.9%) and sacral (25.3%). There was a prevalence of pressure ulcers stage II (68.5%). The mean score of the Braden Scale was 18.3 points, with 45.6% of the elderly were at risk for development of PU. Among seniors, 71.3% had some dependence for activities of daily living and 34.4% were at risk for malnutrition. So much of the institutionalized elderly presents risk for development of PU, demand assistance with bathing, dressing, toileting, transferring from one place to another and feed and is at risk for malnutrition or malnourished.